The Hormetic Morphogen Theory of Curvature and the Morphogenesis and Pathology of Tubular and other Curved Structures - Egil Fosslien (SAGE Publishing, 2009)
In vitro, morphogens such as transforming growth factor (TGF)-β can up-and down-regulate cell growth at low and high concentrations respectively, i.e. they behave like hormetic agents. The hormetic morphogen theory of curvature proposes that in vivo tissue gradients of such morphogens secreted by source cells determine the fate of cells within their gradient fields (field cells) and that morphogen-induced amplitude modulation of field cell mitochondrial adenosine triphosphate (ATP) generation controls field cell growth along the morphogen gradients: At the high concentration end of gradients, field cell ATP generation and field cell growth is reduced. With declining concentrations along the rest of the gradients field cell ATP and growth is progressively less reduced until an equidyne point is reached, beyond which ATP generation and growth gradually increases. Thus, the differential growth rates along the gradients curve the tissue. Apoptosis at very high morphogen concentrations enables lumen and cavity formation of tubular, spherical, cystic, domed, and other curved biological structures. The morphogen concentration, the gradient slope and the hormesis responses of field cells determine the curvature of such structures during developmental morphogenesis, tissue remodeling and repair of injury. Aberrant hormetic morphogen signaling is associated with developmental abnormalities, vascular diseases, and tumor formation.